METHOD OF FUZZY CONTROLLER ADAPTATION.FUZZY CONTROLLER WITH TWO BASIC RULES - Jurayev Aburayhon Xoliqulovich; Ibragimov Islomnur; Eshqobilov Sirojiddin Berdimurodovich (Galaxy International Interdisciplinary Research Journal, 2023)
When writing the work, a fuzzy controller with a double rule base was studied; it was applied to the synthesis of an automated control system. A method for adapting a fuzzy controller has been developed. Adaptation allows the fuzzy controller to automatically compensate for parametric noise that occurs on the control object. In particular, the fuzzy controller controlled the steam temperature at the outlet of the BKZ-75-39 GMA boiler. The program code was written in the Unity Pro XL programming support environment designed to adapt the fuzzy controller.